Assessing biological factors affecting postspeciation introgression. Issue 2 (28th February 2020) - Hamlin, Jennafer A. P.; Hibbins, Mark S.; Moyle, Leonie C.
Abstract: An increasing number of phylogenomic studies have documented a clear "footprint" of postspeciation introgression among closely related species. Nonetheless, systematic genome‐wide studies of factors that determine the likelihood of introgression remain rare. Here, we propose an a priori hypothesis‐testing framework that uses introgression statistics—including a new metric of estimated introgression, D p —to evaluate general patterns of introgression prevalence and direction across multiple closely related species. We demonstrate this approach using whole genome sequences from 32 lineages in 11 wild tomato species to assess the effect of three factors on introgression—genetic relatedness, geographical proximity, and mating system differences—based on multiple trios within the "ABBA–BABA" test. Our analyses suggest each factor affects the prevalence of introgression, although our power to detect these is limited by the number of comparisons currently available. We find that of 14 species pairs with geographically "proximate" versus "distant" population comparisons, 13 showed evidence of introgression; in 10 of these cases, this was more prevalent between geographically closer populations. We also find modest evidence that introgression declines with increasing genetic divergence between lineages, is more prevalent between lineages that share the same mating system, and—when it does occur between mating systems—tends to involve gene flow from more inbreeding to more outbreeding lineages. Although our analysis indicates that recent postspeciation introgression is frequent in this group—detected in 15 of 17 tested trios—estimated levels of genetic exchange are modest (0.2–2.5% of the genome), so the relative importance of hybridization in shaping the evolutionary trajectories of these species could be limited. Regardless, similar clade‐wide analyses of genomic introgression would be valuable for disentangling the major ecological, reproductive, and historical determinants of postspeciation gene flow, and for assessing the relative contribution of introgression as a source of genetic variation.